Analysis of population growth and land use change in Anantnag town of South Kashmir using remote sensing and geographical information system - Malik, Mohammad Imran (Journal of Experimental Sciences, 2012)
The Himalayan region is currently experiencing unplanned and unregulated urban growth. The fast expansion of road linkages, emergence and growth of rural service centers and increased access to markets has facilitated urbanization in Himalayas. The growth in human population is considered not only one of the important causes of urban expansion but also a key driving force of land use land cover (LULC) change. The present study analyses the urban growth of Anantnag town which acts as district headquarter of Anantnag district in South Kashmir Region. The response of various LULC categories to growing population of the town was analyzed using integrated technologies of remote sensing and geographic information system. The results have revealed that the town has registered an increase by 4.37 fold in population and 7.5 fold in area from 1981 to 2011. The arable land has been converted into built-up area and is devoted to various urban land uses. It is therefore highly imperative to analyze and interpret the steering factors of fast urban growth and assess its environmental impacts.